Kompetencje informacyjno-medialne nauczycieli wczesnoszkolnych w zakresie wykorzystywania multimedialnych środków dydaktycznych. Komunikat z badań - Feliniak, Aleksandra (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
The article takes the issue of the place and the role of multimedia teaching resources in the early-school education. Its main objective was to present the real image of competence information – media of young learners education teachers according to my research. Civilization changes cause that school must move with the time and thus keep up with the changing reality. Therefore, in the process of early childhood education multimedia should be already considered. This implies, however, the need to equip teachers with adequate competences.